Enhanced carrier density in Nb-doped SrTiO3 thermoelectrics - Ozdogan, K.; Kahaly, M. Upadhyay; Kumar, S. R. Sarath; Alshareef, H. N.; Schwingenschlogl, U. (AIP Publishing, 2012)
We study epitaxial SrTiO3 interfaced with Nb-doped SrTi1-xNbxO3 (x=0, 0.125, 0.25, 0.375, and 0.5) by full-potential density functional theory. From the electronic band structures obtained by our ab-initio calculations we determine the dependence of the induced metallicity on the Nb concentration. We obtain a monotonous increase of the carrier density with the Nb concentration. The results are confirmed by experiments for SrTi0.88Nb0.12O3 and SrTi0.8Nb0.2O3, demonstrating the predictive power and limitations of our theoretical approach. We also show that the Seebeck coefficient decreases monotonously with increasing temperature. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.3692057]
Keywords: OPTICAL-PROPERTIES; BAND-STRUCTURE; Physics